Security politics in Japan : - Hosoya, Yūichi (Japan Publishing Industry Foundation for Culture, 2019)
This work explores hotly debated security-related matters from a standard viewpoint on international politics and diplomatic history. It also advocates in a bold yet level-headed manner the form Japan’s security should take and the path Japan should follow to make that a reality.